The Influence of Digital Literacy on Students’ Learning Outcomes in the Era of Society 5.0: A Quantitative Study on Senior High School Students - Malik Sofy; Muhammad Permadi (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study examines the influence of digital literacy on student learning outcomes in the Society 5.0 era using a quantitative approach in high school students. Rapid technological changes and digital integration in education require students to have adequate digital literacy skills to be able to access, evaluate, and utilize information effectively. The objectives of the study were to measure students' digital literacy levels, explain the conditions of learning outcomes, and examine the extent to which digital literacy contributes to differences in academic achievement. The study used a correlational design with stratified random sampling in several high schools in the study area. The data collection instrument was a standardized questionnaire to assess digital literacy dimensions including access ability, source evaluation, content utilization, and digital ethics, as well as academic grade documents as indicators of learning outcomes. Data were analyzed using descriptive statistics to map variable profiles and multiple linear regression to examine the influence of digital literacy on learning outcomes, accompanied by classical assumption tests to ensure model validity. The results are expected to show a positive relationship between digital literacy and learning achievement and identify the most influential literacy dimensions. The findings are expected to provide empirical evidence for educators and policymakers to formulate strategies for developing digital competencies in the curriculum and learning practices. The findings are also expected to inspire further research that integrates school context variables and teacher characteristics. This study used strict ethical standards of educational research and participation.